Breakfast consumption among Saudi primary-school children relative to sex and socio-demographic factors - Hazzaa M. Al-Hazzaa; Abdulrahman M. Alhowikan; Maha H. Alhussain; Omar A. Obeid (BMC, 2020)
Abstract Background Breakfast is an important meal that provides essential nutrients and energy. However, few comprehensive studies have reported breakfast habits and related behaviors among Saudi children. This study investigated breakfast consumption patterns and the associations of socio-demographic variables with daily breakfast intake among Saudi children. Methods A multistage stratified cluster random sampling technique was used to select 1051 elementary school boys and girls in Riyadh. Body weight and height were measured and body mass index (BMI) was computed. The breakfast eating habits and behaviors were assessed using a specifically designed self-reported questionnaire that was completed by the children's parents. Results More than 79% of children skipped daily breakfast, with no significant sex difference. Children in private schools consumed breakfast more frequently than those attending public schools. Multivariate analyses showed that boys in private schools had a significantly higher intake of breakfast than that in boys in public schools, yet, boys in public schools had significantly higher BMI than boys in private schools. Using logistic regression while adjusting for confounders showed insignificant effect for parent education. Among breakfast eaters, spread cheese sandwiches were consumed most frequently, followed by fried egg sandwiches and breakfast cereals. Full-fat milk, tea with milk, water, and fruit juice were the most consumed drinks. Girls consumed significantly more fresh fruits during breakfast than did boys. Mothers prepared breakfast at home most of the time (84.5%). Parents appeared mostly satisfied with the breakfast consumed by their child at home and placed high importance on breakfast compared to lunch or dinner. Conclusions The proportion of school children who ate daily breakfast at home was low, which may have implications for children's school performance. Effort is needed to promote daily breakfast consumption among Saudi school children and to introduce appropriate interventions aimed at promoting daily breakfast consumption among Saudi children.